Anger rumination mediates differences between fibromyalgia patients and healthy controls on mental health and quality of life. (6th June 2019) - Toussaint, Loren; Sirois, Fuschia; Hirsch, Jameson; Kohls, Niko; Weber, Annemarie; Schelling, Joerg; Vajda, Christian; Offenbäecher, Martin
Abstract: The present study examined differences between fibromyalgia patients and healthy controls on anger rumination, mental health and quality of life and tested anger rumination as a mediator of patient–control differences in mental health and quality of life. Participants were a propensity score‐matched sample of 58 fibromyalgia patients and 58 healthy controls. Participants completed measures of anger rumination, depression and anxiety and quality of life. Patients were higher than controls on all anger rumination scales and depression and anxiety and lower on quality of life. All anger rumination scales were related to poorer mental health and quality of life. Patient–control differences on mental health and quality of life were mediated by anger rumination. In multiple mediator models, the only subscale with unique mediating effects was anger memories. Anger rumination has potent associations with mental health and quality of life, and differences between patients and controls on mental health and quality of life are partially mediated by differences in anger rumination. Addressing tendencies to ruminate on anger experiences in the care of fibromyalgia patients may offer an important avenue to improved health and quality of life. © 2019 John Wiley & Sons, Ltd.